2015
DOI: 10.1111/nph.13699
|View full text |Cite
|
Sign up to set email alerts
|

Identification and regulation of host genes related to Rice stripe virus symptom production

Abstract: SummaryViral infections cause plant chlorosis, stunting, necrosis or other symptoms. The down-regulation of chloroplast-related genes (ChRGs) is assumed to be responsible for chlorosis.We identified the differentially expressed genes (DEGs) in Rice stripe virus (RSV)-infected Nicotiana benthamiana, and examined the contribution of 75 down-regulated DEGs to RSV symptoms by silencing them one by one using Tobacco rattle virus (TRV)-induced gene silencing.Silencing of 11 of the 75 down-regulated DEGs caused plant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
89
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 77 publications
(92 citation statements)
references
References 53 publications
2
89
0
1
Order By: Relevance
“…Among these DEGs, chloroplast‐ and photosynthesis‐related genes were overrepresented. Several studies have reported that chloroplast‐related or photosynthesis genes are significantly changed during plant virus infection, and that the abnormal expression of these genesis is directly related to symptom development in plant leaves (Bhat et al ., ; Cheng et al ., ; Reuveni et al ., ; Shi et al ., ). As shown in Table S4, photosynthesis‐related antenna proteins, Chl a‐b binding protein and carbon fixation were markedly down‐regulated after virus infection.…”
Section: Discussionmentioning
confidence: 97%
“…Among these DEGs, chloroplast‐ and photosynthesis‐related genes were overrepresented. Several studies have reported that chloroplast‐related or photosynthesis genes are significantly changed during plant virus infection, and that the abnormal expression of these genesis is directly related to symptom development in plant leaves (Bhat et al ., ; Cheng et al ., ; Reuveni et al ., ; Shi et al ., ). As shown in Table S4, photosynthesis‐related antenna proteins, Chl a‐b binding protein and carbon fixation were markedly down‐regulated after virus infection.…”
Section: Discussionmentioning
confidence: 97%
“…The downregulation of CHLI protein, which is involved in chlorophyll biosynthesis, leads to the loss of chlorophyll production and severer chlorosis in a host-specific manner, which is dependent on the CHLI gene sequence [26,27]. Besides the chlorosis, leaf twisting symptom has been attributed to the v-siRNA-mediated silencing of eIF4A in RSV-infected N. benthamiana [25].…”
Section: Introductionmentioning
confidence: 99%
“…The first report of this phenomenon was the targeting of the chlorophyll biosynthetic gene (CHLI) of Nicotiana by siRNAs derived from CMV Y-satellite, resulting in the yellowing of the plant (Shimura et al, 2011; Smith et al, 2011). It has also recently been shown that the eukaryotic translation initiation factor 4A (eIF4A) of Nicotiana benthamiana can be targeted by siRNA derived from Rice stripe virus (RSV), resulting in leaf-twisting and stunting (Shi et al, 2016). These results indicate the complicated function of vsiRNAs during virus-host interaction.…”
Section: Introductionmentioning
confidence: 99%